Structural Equation Modeling on Effects of Community Empowerment and Supplementary Feeding on Health Status and Nutritional Status of Pregnant Women - Lantin Sulistyorini (Universitas Airlangga, 2019)
Introduction: rates of health problems related to a chronic lack of energy in pregnant women in Indonesia remain prevalence. This study aimed to develop community empowerment and supplementary feeding on health status and nutritional status among pregnant women. Methods: the sample included 189 pregnant women living in the six villages in the Jember District. The research used a cluster random sampling technique. The variables included community empowerment, supplementary feeding, health status, and nutritional status of pregnant women. Data analysis was performed using structural equation modeling (SEM) with parameter data estimation using software (Analysis of Moment Structures (AMOS) version 21). Results: estimations of the direct effects were as follows: community empowerment on health status  (0.224), supplementary feeding on health status (0.169), health status on nutritional status of pregnant women (0.001), community empowerment on nutritional status of pregnant women (2.857), supplementary feeding on nutritional status of pregnant women (-0.537), community empowerment on nutritional status of pregnant women through health status (0.000), supplementary feeding on nutritional status of pregnant women through health status (0.000), community empowerment on health status (0.224), supplementary feeding on health status (0.169). Conclusion: community empowerment remains an important key in improving the engagement of women in maternal health issues. Combined intervention with supplementary feeding based on locality may improve the health outcomes.